Magnesium proteinate is more protective than magnesium oxide in heat-stressed quail - Şahin, Nurhan; Onderci, M; Şahin, Kazım; Cikim, G; Küçük, Ömer (Elsevier Science Inc, 2005)
We evaluated the effects of dietary supplementation with Mg-oxide and Mg-proteinate on performance; nutrient digestibilities; malondialdehyde (MDA) concentrations in serum, liver, and thigh meat; and serum cholesterol and triacylglycerol concentrations in Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature. The birds (n = 360; 10 d old) were randomly assigned to 12 treatment groups consisting of 6 replicates of 5 birds each in a 2 x 2 X 3 factorial arrangement (temperature, Mg source, Mg level). Birds were maintained in temperature-control led rooms at 22 degrees C for 24 h/d or 34 degrees C for 8 h/d (0900-1700 h) and fed a basal diet or that diet supplemented with 1 or 2 g Mg-oxide or Mg-proteinate/kg of diet. Heat exposure decreased (P = 0.0001) live weight gain, feed intake, feed efficiency, and carcass weight in quail fed the basal diet. A linear increase in feed intake (P = 0.008) and body weight (P = 0.001), and improvements in feed efficiency (P = 0.001), carcass weight (P < 0.0001), digestibility of dry matter, organic matter, crude protein, and ether extract were found in Mg-supplemented, heat-stressed quail. The effects of Mg-proteinate were greater than those of Mg-oxide (P :5 0.0001). Serum Mg (P = 0.001) concentration increased, whereas the concentration of MDA in serum (P = 0.0001), liver (P = 0.04), and thigh meat (P = 0.0001) and serum triglycericle and cholesterol concentrations decreased linearly (P = 0.001) with the level of Mg in the diet. Interactions between dietary Mg source, temperature, and level of supplementation (P <= 0.05) were found for several variables. Results of the present study suggest that supplementation with Mg-proteinate is more protective than Mg-oxide in reducing the negative effects of heat stress in quail. J. Nutr. 135: 1732-1737, 2005.
Keywords: magnesium; oxidative stress; performance; quail